Improvement of students' digital literacy through the development of android-based Smart Edu learning media on plant breeding material - Fitriasih, Fajarani; Faros, Arrum Ardila; Gunarsih, Dwi; Ristanto, Rizhal Hendi; Isfaeni, Hanum (Department of Biology Education, Universitas Pendidikan Indonesia, 2024)
This study intends to increase students' digital literacy abilities through the implementation of Smart Edu learning media in plant breeding material. This is a research and development project. Peer reviewers, material specialists, media experts, and student trials are used to evaluate products. Digital literacy and media assessment questionnaires were used to gather research data. The investigation's findings are: 1) According to scientific phases, the Android-based Smart Edu learning media was created, and its features include an eye-catching visualization display, ease of use, and content that aligns with the goals of plant growth and development; 2) according to material expert tests, android-based smart edu learning media on plant growth and development material that has been developed is suitable for use in learning when viewed from the perspective of content assessment or the learning material's contents, which are included in the very good category; 3) learning with android-based smart edu media has significantly improved digital literacy when compared to conventional learning. The development and application of Android-based smart educational learning materials demonstrate that their use is both practical and efficient in enhancing students' digital literacy. Further study should be done to create iOS and Android-based applications as well